Pengaruh Kepemimpinan Islami Terhadap Kinerja Tenaga Kefarmasian di Instalasi Farmasi Rumah Sakit Tk. III Bhakti Wira Tamtama Semarang: The Influence of Islamic Leadership on the Performance of Pharmacy Personnel in the Kindergarten Hospital Pharmacy Installation Tk. III Bhakti Wira Tamtama Semarang - Apriani, Welin Devsi; Fathnin, Fildza Huwaina (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2025)
Content Islamic leadership is expected to be able to stimulate employee motivation to achieve optimal performance. Leadership is related to the performance of pharmaceutical personnel because leaders plan, inform, make and evaluate various decisions that must be implemented in the hospital, therefore, leadership is an important factor in employee performance. This research aims to determine the influence of Islamic Leadership on the Performance of Pharmacy Personnel in the Kindergarten Hospital Pharmacy Installation Tk. III Bhakti Wira Tamtama Semarang. This research is a quantitative type with analytical methods. Sampling used a questionnaire instrument, each variable consisting of 6 questions which were distributed directly in the Hospital Pharmacy Installation Tk. III Bhakti Wira Tamtama Semarang. The sampling technique used in this research was a saturated sampling technique with a total sample of 18 respondents. Then look for the influence between the two variables using the Spearman rank correlation test. Rresults of this study show a significant value of 0.003 <0.05 with a correlation coefficient value of 0.661. Conclusion, there is a significant influence between Islamic leadership on the performance of pharmaceutical staff in the Hospital Pharmacy Installation Tk. III Bhakti Wira Tamtama Semarang with a strong and positive correlation relationship, namely the better the Islamic leadership, the better the performance of the pharmaceutical staff. Keywords: Islamic Leadership, Performance, Pharmacy Abstrak Kepemimpinan islami diharapkan mampu memacu motivasi karyawan untuk tercapainya kinerja yang optimal. Kepemimpinan berhubungan dengan kinerja tenaga kefarmasian kerena pemimpin yang merencanakan, menginformasikan, membuat, dan mengevaluasi berbagai keputusan yang harus dilaksanakan dalam rumah sakit oleh karena itu, kepemimpinan salah satu faktor penting dalam kinerja karyawan. Penelitian ini bertujuan untuk mengetahui pengaruh Kepemimpinan Islami terhadap Kinerja Tenaga Kefarmasian di Instalasi Farmasi Rumah Sakit Tk. III Bhakti Wira Tamtama Semarang. Penelitian ini masuk kedalam jenis kuantitatif dengan metode analitik. Pengambilan sampel menggunakan instrument kuesioner yang masing-masing variabel terdiri atas 6 pertanyaan yang disebar secara langsung di di Instalasi Farmasi Rumah Sakit Tk. III Bhakti Wira Tamtama Semarang. Teknik pengambilan sampel yang digunakan dalam penelitian ini adalah teknik sampling jenuh dengan total sampel sebanyak 18 responden. Kemudian dicari pengaruh antara kedua variabel dengan menggunakan uji korelasi rank spearman. Hasil penelitian ini menunjukkan nilai signifikan 0,003 < 0,05 dengan nilai koefisin korelasi 0,661. Kesimpulannya terdapat pengaruh yang signifikan antara kepemimpinan islami terhadap kinerja tenaga kefarmasian di Instalasi Farmasi Rumah Sakit Tk. III Bhakti Wira Tamtama Semarang dengan hubungan korelasi yang kuat dan positif yaitu semakin bagus kepemimpinan islami maka semakin bagus pula kinerja tenaga kefarmasian. Kata Kunci: Kapemimpinan Islami, Kinerja, Kefarmasian